Surface disinfection and protective masks for SARS‐CoV‐2 and other respiratory viruses: A review by SIdP COVID‐19 task force. (6th October 2020) - Barbato, Luigi; Bernardelli, Francesco; Braga, Giovanni; Clementini, Marco; Di Gioia, Claudio; Littarru, Crisitnano; Oreglia, Francesco; Raspini, Mario; Brambilla, Eugenio; Iavicoli, Ivo; Pinchi, Vilma; Landi, Luca; et al.
Abstract: Objectives: Primary focused question for this systematic review (SR) was "Which is the evidence about surfaces decontamination and protection masks for SARS‐Cov‐2 in dental practice?" Secondary question was " Which is the evidence about surfaces decontamination and protection masks against airborne pathogens and directly transmitted viral pathogens causing respiratory infections?" Materials and Methods: PRISMA guidelines were used. Studies on surface decontamination and protective masks for SARS‐CoV‐2 in dental practice were considered. Studies on other respiratory viruses were considered for the secondary question. Results: No studies are available for SARS‐CoV‐2. Four studies on surface disinfection against respiratory viruses were included. Ethanol 70% and sodium hypochlorite 0, 5% seem to be effective in reducing infectivity by > 3log TCID. Four RCTs compared different types of masks on HCW. The single studies reported no difference for laboratory‐diagnosed influenza, laboratory‐diagnosed respiratory infection, and influenza‐like illness. A meta‐analysis was not considered appropriate. Conclusions: There is lack of evidence on the efficacy of surface disinfection and protective masks to reduce the spread of SARS‐CoV‐2 or other respiratory viruses in dentistry. However, the consistent use of respirator and routine surface disinfection is strongly suggested. There is urgent need of data on the efficacy of specific protection protocols for dental HCW against viral infections.